Rethinking Muslim Identity in Diaspora: Beyond Orientalism in Aliya Husain’s Neither This Nor That - Asiyah, Nur; Nurjanah, Hidayatul; Hafizah, Noer (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research explores Indian-American Identity representation in the diaspora context as depicted in the novel Neither This Nor That by Aliya Husain. In Exploring issues of Identity, culture, and social tension, this research applies the theory of Orientalism by Edward Said and Identity Negotiation by Ting-Tomey. This qualitative descriptive study analyzes textual data to examine how the prominent figure negotiates her identity within the contexts of religion, culture, and social interaction. The findings conclude that Identity is shaped not only by her ambivalence between East and West but also by personal agency and cultural environment. By rethinking these theories in the current context, this study argues that traditional frameworks fall short of fully capturing the dynamic nature of modern Muslim Identity. Therefore, it suggests a more contextual and flexible understanding of Identity negotiation in diaspora literature. This research contributes to ongoing discussions in postcolonial studies and contemporary literary analysis.